MicroRNA‐137 suppresses tongue squamous carcinoma cell proliferation, migration and invasion. (30th August 2016) - Sun, Lanying; Liang, Jin; Wang, Qibao; Li, Zhaoyuan; Du, Yi; Xu, Xin
Abstract: Objectives: Tongue squamous cell carcinoma (TSCC) is the most frequent type of oral malignancy. Increasing evidence has shown that miRNAs play key roles in many biological processes such as cell development, invasion, proliferation, differentiation, metabolism, apoptosis and migration. Materials and methods: qRT‐PCR analysis was performed to measure miR‐137 expression. CCK‐8 analysis, cell colony formation, wound‐healing analysis and invasion were performed to detect resultant cell functions. The direct target of miR‐137 was labelled and measured by luciferase assay and Western blotting. Results: We demonstrated that expression of miR‐137 was downregulated in TSCC tissues compared to matched normal ones. miR‐137 expression was downregulated in TSCC lines (SCC4, SCC1, UM1 and Cal27) compared to the immortalized NOK16B cell line and normal oral keratinocytes in culture (NHOK). In addition, we have shown that miR‐137 expression was epigenetically regulated in TSCCs. Overexpression of miR‐137 suppressed TSCC proliferation and colony formation. Ectopic expression of miR‐137 promoted expression of the epithelial biomarker, E‐cadherin, and inhibited the mesenchymal biomarker, N‐cadherin, as well as vimentin and Snail expression, indicating that miR‐137 suppressed TSCC epithelial‐mesenchymal transition (EMT). We also showed that ectopic expression of miR‐137 inhibited TSCC invasion and migration. In addition, we identified SP1 as a direct target gene of miR‐137 in SCC1 cells. SP1 overexpression rescued inhibitory effects exerted by miR‐137 on cell proliferation and EMT. Conclusions: These results indicate that miR‐137 acted as a tumour suppressor in TSCC by targeting SP1.